CORAK PENAFSIRAN ACARA SERAMBI ISLAMI TVRI DAN RELEVANSINYA TERHADAP PENDIDIKAN DIVERSITAS SOSIO- KULTURAL SELAMA MASA PANDEMI - Darwis, Yuliandre; Hude, Darwis; Hariyadi, Muhammad (Departemen Ilmu Komunikasi Universitas Andalas, 2024)
This study examines the interpretation patterns in the Serambi Islami TVRI program during the 2020-2021 pandemic, focusing on social interpretation patterns (al-Adabī wa al-Ijtima’ī). The themes addressed in these interpretations include values such as mutual cooperation, media ethics, family roles, radicalism, rahmatan lil 'Alamin, the importance of dhikr, manners in religious gatherings, and the roles of husbands and wives in the family. The aim of this research is to explore the interpretations conveyed by the speakers and their relevance to informal education in Indonesia, particularly in the socio- cultural education context. The method used is descriptive analysis, with contextual and textual approaches in delivering the interpretations. The results show that most speakers used the ijmali interpretation method with a more contextual approach, although there was variation in the delivery methods. This dissertation also found similarities with Albert Bandura's social learning theory, where new behavior is learned through observation and imitation. On the other hand, this theory differs from nativism, which considers that education does not influence human development. The Serambi Islami TVRI program is considered relevant to socio-cultural diversity education in Indonesia, as it teaches values that align with the characteristics of Indonesian society, such as brotherhood, equality, tolerance, deliberation, mutual assistance, and justice. This research concludes that the program contributes to informal education accessible to the broader public without requiring formal education.